(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present research is an attempt to understand the role of “green” in the context of green marketing communications that can influence the green buying decisions of people. The existing research in this area has been examined to identify the major thrust areas that the firms adhering to green marketing strategies are emphasizing to influence their customers. An investigative framework comprising of prime theme of advertisements of such firms is created that identifies and classifies various stakeholders, potentially impacted through the environmentally friendly effort of a firm. It was observed that the customers that are sensitised to the green buying in the area of Prayagraj, do notice the message of the advertisement and carry difference in opinions on the impact of such green marketing communications but the reflection in their buying preferences are not consistent with their opinions.